Veteran-derived cerebral organoids display multifaceted pathological defects in studies on Gulf War Illness - Yates, Philip L.; Case, Kendra; Sun, Xiaohuan; Sullivan, Kimberly; Baas, Peter W.; Qiang, Liang (Frontiers in Cellular Neuroscience, 2022)
Approximately 30% of the veterans who fought in the 1991 Gulf War (GW) suffer from a disease called Gulf War Illness (GWI), which encompasses a constellation of symptoms including cognitive deficits. A coalescence of evidence indicates that GWI was caused by low-level exposure to organophosphate pesticides and nerve agents in combination with physical stressors of the battlefield. Until recently, progress on mechanisms and therapy had been limited to rodent-based models. Using peripheral blood mononuclear cells from veterans with or without GWI, we recently developed a bank of human induced pluripotent stem cells that can be differentiated into a variety of cellular fates. With these cells, we have now generated cerebral organoids, which are three-dimensional multicellular structures that resemble the human brain. We established organoid cultures from two GW veterans, one with GWI and one without. Immunohistochemical analyses indicate that these organoids, when treated with a GW toxicant regimen consisting of the organophosphate diisopropyl fluorophosphate (a sarin analog) and cortisol (to mimic battlefield stress), display multiple indicators consistent with cognitive deficits, including increased astrocytic reactivity, enhanced phosphorylation of tau proteins, decreased microtubule stability, and impaired neurogenesis. Interestingly, some of these phenotypes were more pronounced in the organoids derived from the veteran with GWI, potentially reflecting a stronger response to the toxicants in some individuals compared to others. These results suggest that veteran-derived human cerebral organoids not only can be used as an innovative human model to uncover the cellular responses to GW toxicants but can also serve as a platform for developing personalized medicine approaches for the veterans.